Contracts for clean development: The role of technology transfers - Katrin Millock (Fondazione Eni Enrico Mattei (FEEM), 2000)
The Clean Development Mechanism (CDM) offers abatement cost savings under the Kyoto Protocol by allowing credits for emission reductions obtained in signatory developing countries. The paper shows that it is necessary to include technology transfers in the CDM to obtain correct incentives for emission reductions when there are monitoring difficulties.
Keywords: Q20; D82; 330; Global climate change; asymmetric information; Clean Development Mechanism; optimal incentives; technology transfers; Klimaschutz; Umweltabkommen; Internationale Transferzahlungen; Technologietransfer; Ökonomischer Anreiz; Theorie; Welt